Gender differences in relation of gender role attitudes and happiness—a mixed-methods research from China - Chen, Yanan; Zhang, Xubin (Frontiers in Psychology, 2024)
The gender equality movement represents a monumental advancement in human civilization, liberating countless women worldwide politically, socially, and economically. Intuitively, women are expected to experience greater happiness from the concept of gender equality, while men may see diminished benefits as gender oppression fades away. However, in China, the data indicates a surprising trend: men seem to derive more happiness from gender equality than women. This phenomenon often occurs in countries where gender equality has been achieved, known as the gender equality paradox, while it is relatively rare in countries in transition. In response to this contradiction, a mixed-methods research approach was adopted, utilizing cross-sectional data from the Chinese General Social Survey (CGSS) and conducting interviews with 10 participants. In the context of China, happiness increases with gender-egalitarian attitudes, with men experiencing a more pronounced boost. Upon investigation, Women with egalitarian values, unlike traditional counterparts, are less tolerant of sexual unfairness, limiting women’s happiness growth. Conversely, Chinese men with an equality mindset find greater happiness through benefits like economic relief, reduced family responsibilities, and positive emotional values. To address this incongruity, The government and society should collaborate to overcome the resistance encountered in the practical realization of gender equality, eliminate gender discrimination and opposition, and ensure alignment between the concept and practice of gender equality.